Existentialism : a very short introduction - Flynn, Thomas R. (Very short introductions ;, 2006)
Sartre, Nietzsche, Heidegger, Kierkegaard, de Beauvoir Merleau-Ponty and Camus were some of the most important existentialist thinkers. This book provides an account of the existentialist movement, and of the themes of individuality free will, and personal responsibility which make it a 'philosophy as a way of life'.